Media and conflict dynamics in a globalizing word - Avila, Flor María; Chingono, Mark; Sultan, María; Djuraev, Qodir (Frónesis)
The aim of this study is to examine the impact of media on conflict resolution in a globalizing world. What role does the media play in conflict resolution? Why and how do some conflicts receive international attention and positive media coverage, while others are ignored or portrayed negatively? This study cannot provide definitive answers; instead it seeks to invite further discussion by highlighting the significance of a few select cases of successful and unsuccessful conflict resolution. Its conclusion is that human rights violations are often used by international media for ideological purposes instead of focusing on the actual victimization of people by those who control the institution of violence.